Challenges of public procurement in EU funded projects - Marko Šostar; Ana Marukić (Management : Journal of Contemporary Management Issues, 2017)
Membership in the European Union implies adjustment of EU projects to the rules of Structural Funds, but also adoption of legal regulations, thus influencing the process of implementation of the public procurement in EU funded projects. Each successful applicant who expressed the need for procurement of goods, services and works of a certain value, must respect the principles of public procurement. Irregularities in the procurement process can lead to the failure of returning the EU funds even several years after the end of the project. Therefore, the knowledge and proper implementation of public procurement is the main precondition for the correct implementation of each project. In order to obtain information about the current absorption capacity of the public procurement liable parties, and to identify key obstacles that stakeholders face in procurement procedures, the research was conducted by surveying 30 entities that are subject of public procurement in Croatia. Research results imply the poor quality of public procurement in the implemented projects, which often results in financial corrections, disapproving project reports, etc.